STUDENTS’ PERCEPTION OF SCHOOL ENVIRONMENT AND ITS IMPACT ON ENGLISH ACADEMIC ACHIEVEMENT - Eka Pratiwi Sudirman (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This research aimed to find out: (1) the students’ perception on the impact of school environment on English academic achievement at SMA Negeri 17 Makassar, and (2) the school facilities provided to improve students' English academic achievement. This research employed a qualitative method. The subjects of this research were twenty students of SMA Negeri 17 Makassar, which were recruited through a purposive sampling technique. The data of this research were collected through interviews. The obtained data were analyzed in four major phases: data collection, data display, data condensation, and conclusion. The result of this research is presented descriptively in order to reveal the students’ perception comprehensively. (1) It was found that the impact of school environment on student English academic achievement based on students perception: 60% students believed the impact was significant, 30% students believed the impact was not significant, and 10% students believed there was no impact of school environment on English academic achievement and (2) there are two major facilities that has impact on students’ English academic achievement, they are library and language-based extracurricular (SEEDS).